2015
DOI: 10.1155/2015/592523
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Tumour Angiogenesis: A Preventive Role of Metformin against Breast Cancer

Abstract: Metformin is one of the most widely prescribed antidiabetics for type 2 diabetes. A critical role of metformin against tumorigenesis has recently been implicated, although several studies also reported the lack of anticancer property of the antidiabetics. Given the controversies regarding the potential role of metformin against tumour progression, the effect of metformin against breast, cervical, and ovarian tumour cell lines was examined followed by in vivo assessment of metformin on tumour growth using xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…The findings that metformin blocked vascular invasion of thyroid tumors of Thrb PV/PV Pten +/− mice are in line with the reports in which the anti-angiogenic effects of metformin were described in colon cancer [39], HER2+ tumor cells [40] and breast tumors [41, 42]. In colon cancer, metformin was shown to down regulate tumor angiogenesis and augment the antitumor effect oxaliplatin [39].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The findings that metformin blocked vascular invasion of thyroid tumors of Thrb PV/PV Pten +/− mice are in line with the reports in which the anti-angiogenic effects of metformin were described in colon cancer [39], HER2+ tumor cells [40] and breast tumors [41, 42]. In colon cancer, metformin was shown to down regulate tumor angiogenesis and augment the antitumor effect oxaliplatin [39].…”
Section: Discussionsupporting
confidence: 87%
“…In HER2+ tumor cells, metformin treatment decreased microvessel-induced inhibition of tumor angiogenesis [40]. In breast tumors, metformin reduced tumor microvessel density and attenuated tumor angiogenesis [41, 42]. While metformin was shown to have anti-neoplastic effects in diabetic patients with differentiated thyroid cancer [25], whether metformin has anti-angiogenic effects in thyroid cancer progression remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…8 Interestingly, another study has indicated that administration of 0.1 mM metformin for 24 hours is able to supress 50% of HeLa cell growth. 23 An inhibitory effect of metformin is also observed in some thyroid cancer cell lines, which incubated with various doses of metformin for 24-72 hours. 18 During 24 hour incubation, a higher dose of metformin (≥40 mM) was required for inhibition of cell proliferation of thyroid cancer cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…In detail, this study found that the metformin inhibited solid tumors in the normal mice by increasing the number of CD8 + tumor-infiltrating lymphocytes. In addition, the metformin also could reduce insulin resistance and attenuate tumor angiogenesis [30][31][32]. By elucidating the mechanisms that are involved in the anticancer effect of metformin, could be benefit for performing better therapeutic strategies, improve the prognosis of patients with T2D and cancer.…”
Section: Discussionmentioning
confidence: 99%